Self-Directed Learning in STEM Teaching and Learning: A Systematic Review of Empirical Evidence - Mercado, Justine (Scientechno: Journal of Science and Technology, 2024)
Despite the growing popularity of self-directed learning (SDL) research, the impacts of this approach on science, technology, engineering, and mathematics teaching and learning (STEM-TL) still need to be well documented. To address this issue, this systematic review analysed and synthesised content from 50 published articles in the form of study characteristics, research methods, learning theories and strategies, technology platforms, impacts, challenges, and research opportunities related to the application of SDL in STEM-TL retrieved from the Web of Science (WoS) database and Scopus within the last five years. The studies examined reveal evidence that the use of SDL in STEM-TL has been quite diverse and holds promise for student success in acquiring and mastering 21st-century skills. Unfortunately, only some studies anticipate other potential concerns, such as early SDL application, student character degeneration, uncontrolled technological progress, and an unknown future educational environment. This systematic review gives a summary of what was found, which can be used to build a framework that teachers, schools, and policymakers can use in current and future STEM-TL settings and curricula.